Rural Land Concentration & Protected Areas: Recent Trends from Montana and Greater Yellowstone. Issue 6 (3rd June 2022) - Haggerty, Julia H.; Epstein, Kathleen; Gosnell, Hannah; Rose, Jackson; Stone, Michael
Abstract: Where agricultural land use and biodiversity conservation values overlap, conservation science has tended to focus on the challenges posed by land ownership fragmentation. However, the dynamics of land concentration also affect rural landscapes and economies upon which biodiversity conservation increasingly depends. In this study, we provide a methodological approach to measuring concentration using parcel-level data to generate a description of private landownership trends at the boundary of the Northern Rockies and the Northern Great Plains, two ecoregions of global conservation significance. Across our 25m-acre study region in Montana, USA concentration in large land ownership increased by 7 percent between 2005 and 2018. Growth of a county's largest landholding through the agglomeration of properties into a single mega-estate emerges as a recurring trend. Other drivers contribute to concentration, suggesting a mix of conservation opportunities and challenges that merits further research and consideration by academic and resource management stakeholders.